#TITLE_ALTERNATIVE# - Amru Reza (nim: 101 03 023), Mohamad
Abstract: Markov stochastic process has been widely used in both industries and researches, such as marketing, insurance, weather forecast, and bioinformatics. Mathematical problems that interesting to be studied are order, determination of the size of the order; convergence and stationary, and estimation of t step transition probability matrix, Pt. In this final project, there are two purposes. First, to find a procedure to calculate Pt for r order Markov chain, Ō(r), r integer and r > 1. It is conducted by defining a one step transition probability matrix P which size is nr x n where n is the number of states and r is the size of the order. Second, to improve the Chi-Square test as goodness of fit test in determining the order of a Markov chain. Homo Sapiens nucleotide sequence, which has been observed by genetic experts, was collected as real data to support this invention.